2ln(x)=ln(21)

Simple and best practice solution for 2ln(x)=ln(21) equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 2ln(x)=ln(21) equation:


Simplifying
2ln(x) = ln(21)

Multiply ln * x
2lnx = ln(21)

Reorder the terms for easier multiplication:
2lnx = 21ln

Solving
2lnx = 21ln

Solving for variable 'l'.

Move all terms containing l to the left, all other terms to the right.

Add '-21ln' to each side of the equation.
-21ln + 2lnx = 21ln + -21ln

Combine like terms: 21ln + -21ln = 0
-21ln + 2lnx = 0

Factor out the Greatest Common Factor (GCF), 'ln'.
ln(-21 + 2x) = 0

Subproblem 1

Set the factor 'ln' equal to zero and attempt to solve: Simplifying ln = 0 Solving ln = 0 Move all terms containing l to the left, all other terms to the right. Simplifying ln = 0 The solution to this equation could not be determined. This subproblem is being ignored because a solution could not be determined.

Subproblem 2

Set the factor '(-21 + 2x)' equal to zero and attempt to solve: Simplifying -21 + 2x = 0 Solving -21 + 2x = 0 Move all terms containing l to the left, all other terms to the right. Add '21' to each side of the equation. -21 + 21 + 2x = 0 + 21 Combine like terms: -21 + 21 = 0 0 + 2x = 0 + 21 2x = 0 + 21 Combine like terms: 0 + 21 = 21 2x = 21 Add '-2x' to each side of the equation. 2x + -2x = 21 + -2x Combine like terms: 2x + -2x = 0 0 = 21 + -2x Simplifying 0 = 21 + -2x The solution to this equation could not be determined. This subproblem is being ignored because a solution could not be determined. The solution to this equation could not be determined.

See similar equations:

| 17=32 | | 40=16t^2+88t | | 20=(1/4c) | | 75=3x^2-9 | | 18x+5=20x+1 | | log*(x+11)-log(2)=log*(5x+1) | | 21=-7u | | 18+5=20+1 | | 2/3x-16 | | (x/4)=3 | | 3y=8-7y-1 | | (12b-6)-(7-18b)= | | (2n^2+4n+3)(2n-3)= | | (-7x)(-1/7) | | 76.9-34.782= | | 8x+3.5=36 | | 6-10=1 | | 16x^2+7x-9=0 | | 3(1+2y)-5=6y-2 | | .468*4.8= | | -14.49-3.9d=3.3(d+3.9) | | 5=3n-n+5 | | 576*.6= | | -2x^2+20x=-82 | | a^2-4a-24+6a= | | 3(1-2y)-5=6y-2 | | 2a-10=44+8a | | -2d+18-4b=60 | | 9x+2+5x+4= | | 4x^2=488 | | (x-30)*.5=100 | | -6(1a-2b)-2(5b-4a)= |

Equations solver categories